DETECTION OF THE BOVINE VIRAL DIARRHEA ANTIBODIES - I. V. Goraichuk; V. I. Bolotin; A. P. Gerilovych; O. S. Solodyankin; R. O. Kucheryavenko; V. V. Kucheryavenko (Biotechnologia Acta, 2013)
Bovine viral diarrhea is a widespread infection of cattle that has a wide range of clinical symptoms in domestic and wild ruminants. It is a major problem in cattle and causes significant economic losses in the cattle industry. The virus infects bovines of all ages and causes both immunosuppression and reproductive, respiratory and digestive disorders. Persistently infected cattle are the main factor in transmission of the disease between and among herds. Comparative results of antibodies presence received by two methods of enzymoimmunoassay and virus neutralization test are given in the paper. During the work, 1010 samples of blood serum of cattle from three farms in the Kharkiv region were selected and analyzed. Bovine viral diarrhea virus concerning antibodies were found by enzymoimmunoassay in 704 samples (69.7%) using commercial kit and in 690 samples (68.3%) using in house method. After results clarification by virus neutralization test, bovine viral diarrhea antibodies were found in 712 samples (70.5%). Immunoenzyme analysis is recommended for mass screening of cattle for viral diarrhea occurrence. The results confirm that the sensitivity immunoenzyme analysis satisfies the requirements of the diagnostic methods. Using the neutralization reaction of viruses as the «gold standard» of serological methods, it is appropriate to clarify the results of immunoenzyme analysis. Since the results contain a signi ficant number of false positive results, it is necessary to carry out comprehensive studies using both serological and molecular genetics methods.